Turtles and Tortoises of the World During the Rise and Global Spread of Humanity: First Checklist and Review of Extinct Pleistocene and Holocene Chelonians - Rhodin, Anders G. J. (2015)
We provide a first checklist and review of all recognized taxa of the world’s extinct Pleistocene and Holocene (Quaternary) turtles and tortoises that existed during the early rise and global expansion of humanity, and most likely went extinct through a combination of earlier hominin (e.g., Homo erectus, H. neanderthalensis) and later human (H. sapiens) exploitation, as well as being affected by concurrent global or regional climatic and habitat changes. This checklist complements the broader listing of all modern and extant turtles and tortoises by the Turtle Taxonomy Working Group (2014). We provide a comprehensive listing of taxonomy, names, synonymies, and stratigraphic distribution of all chelonian taxa that have gone extinct from approximately the boundary between the Late Pliocene and Early Pleistocene, ca. 2.6 million years ago, up through 1500 AD, at the beginning of modern times. We also provide details on modern turtle and tortoise taxa that have gone extinct since 1500 AD. This checklist currently includes 100 fossil turtle and tortoise taxa, including 84 named and apparently distinct species, and 16 additional taxa that appear to  represent additional valid species, but are only identified to genus or family. Modern extinct turtles and tortoises include 8 species, 3 subspecies, and 1 unnamed taxon, for 12 taxa. Of the extinct fossil taxa, terrestrial tortoises of the family Testudinidae (including many large-bodied island forms) are the most numerous, with 60 taxa. When the numbers for fossil tortoises are combined with the 61 modern (living and extinct) species of tortoises, of the 121 tortoise species that have existed at some point since the beginning of the Pleistocene, 69 (57.0%) have gone extinct. This likely reflects the high vulnerability of these large and slow terrestrial (often insular) species primarily to human exploitation. The other large-bodied terrestrial turtles, the giant horned turtles of the family Meiolaniidae, with 7 taxa (also often insular), all went extinct by the Late Holocene while also exploited by humans. The total global diversity of turtles and tortoises that has existed during the history of hominin utilization of chelonians, and that are currently recognized as distinct and included on our two checklists, consists of 336 modern species and 100 extinct Pleistocene and Holocene taxa, for a total of 436 chelonian species. Of these, 109 species (25.0%) and 112 total taxa are estimated to have gone extinct since the beginning of the Pleistocene. The chelonian diversity and its patterns of extinctions during the Quaternary inform our understanding of the impacts of the history of human exploitation of turtles and the effects of climate change, and their relevance to current and future patterns.